Monogenic diabetes: the role of mitochondrial dysfunction and endoplasmic reticulum stress - Ozsu, Elif (Frontiers in Clinical Diabetes and Healthcare, 2025)
A diverse range of disorders resulting from various pathophysiological mechanisms are represented by rare forms of diabetes. To date, variants in at least 25 different genes have been identified. Although these forms account for only approximately 6% of all diabetes cases, accurate diagnosis is essential for effective treatment and personalized disease management. Most of these subtypes are monogenic, syndromic, or related to structural abnormalities, providing crucial insights into the genetic and physiological underpinnings of glucose regulation. Clinical clues, such as an early age at onset, the absence of autoantibodies, atypical disease progression, low insulin requirements, and the presence of multi-organ involvement, may indicate a non-classical diabetes phenotype. The classification and recognition of these rare types are clinically significant, especially as advances in genetic technologies continue to expand our understanding of disease mechanisms and therapeutic options. Significantly, the study of rare diabetes forms contributes not only to individualized care but also to the development of novel therapeutic strategies for more common types such as type 1 and type 2 diabetes. The improved understanding of beta-cell function and its genetic regulation through these models has enabled the emergence of precision medicine approaches that extend beyond conventional glycemic control. Mitochondrial diabetes results from mitochondrial defects that impair energy metabolism in pancreatic β-cells, while endoplasmic reticulum (ER) stress—induced by the accumulation of misfolded proteins—triggers β-cell apoptosis. These convergent mechanisms disrupt insulin secretion and glycemic homeostasis, driving diabetes pathogenesis. Elucidating the molecular interplay between mitochondrial dysfunction and ER stress may advance the understanding of disease progression and facilitate the development of targeted therapeutic strategies. This review summarizes the current knowledge on rare forms of diabetes, emphasizing their diagnostic value and therapeutic potential.